Gastric and colonic metastasis from NSCLC: A very unusual case report. Issue 2 (14th January 2022) - Catalano, Martina; Marini, Andrea; Ferrari, Katia; Voltolini, Luca; Cianchi, Fabio; Comin, Camilla Eva; Castiglione, Francesca; Roviello, Giandomenico; Mini, Enrico
Abstract: Rationale: Lung cancer is the most common cause of cancer-related deaths worldwide. Approximately 50% of patients is metastatic at diagnosis and the most common metastatic sites are bone, lungs, brain, adrenal glands, liver, and extra thoracic lymph nodes. The occurrence of gastrointestinal metastasis from lung carcinoma is rare and seems more commonly related to small cell lung cancer compared to non-small cell lung cancer (NSCLC). Patient information and diagnosis: A 78-year-old man with completely surgically resected NSCLC and no initial evidence of distant metastases developed colon and gastric metastases 7 months after diagnosis, confirmed by serial radiological examinations and endoscopic biopsies. Interventions: The patient was subjected to total gastrectomy with D2 lymph node dissection plus partial colectomy for intraoperative detection of a transverse colon neoformation. Subsequent instrumental imaging showed bilateral lung tumor recurrence, treated with gemcitabine monotherapy for 8 months as first line chemotherapy for lung adenocarcinoma. Results: The patient presented complete response to therapy and was disease-free for 4 years. Lessons: Colonic and gastric metastasis are very infrequent in NSCLC. The resection of gastrointestinal metastasis may provide benefits in terms of both symptom control and survival in patients properly selected.